Adébáyọ̀ Fálétí: The Portrait of a Cultural Connoisseur - Tunji Ọlaọpa (Yoruba Studies Review)
The recent death of Alàgbà Adébáyọ̀ Fálétí, father, husband, writer, poet and journalist, may not qualify as a national event. Yet we have just lost a cultural hero whose lifestyle and literary activities cut right to the heart of living for oneself and living for others. Bàbá Fálétí could pass for an ordinary farmer in Òkè-Ògùn, as well as a professor of literature at any Ivy League university across the world. Thus, one immediate point of association with his memory is his easy going and quiet force of character that, I suspect, was moulded in the cauldron of a life lived within the character-forming context of the Yorùbá communal values and ethos. No wonder Alàgbà Fálétí eventually became a sturdy man of culture whose understanding projected a firm conviction about what culture can enable us to do.